STRONGLY BOUNDED REPRESENTING MEASURES AND CONVERGENCE THEOREMS - GHENCIU, IOANA; LEWIS, PAUL (Glasgow mathematical journal, 2010)
Let K be a compact Hausdorff space, X a Banach space and C(K, X) the Banach space of all continuous functions f: K → X endowed with the supremum norm. In this paper we study weakly precompact operators defined on C(K, X).